Conceptual Issues of the Necessity of the Legal Formation Stage and the Prerequisites for Implementation in the RA. - Martirosyan, Hayk (Bulletin of Yerevan University C: Jurisprudence, 2024)
Improving the quality of legal norms has a significant impact on the process of forming a strategic and programmatic state through the improvement of the quality of life of society representatives, the comfort of life, and the development of legal awareness. From the point of view of the realization of the goal, it is important to develop and implement the tools and substantive proposals that will lead to the improvement of the quality of legal norms. Ensuring broad public involvement in the process of forming legal norms, introducing real and realistic mechanisms that will take into account the best foreign experience, localizing it to local conditions and public demands, is of primary importance in this matter. Legal formation deserves special attention as the primary stage of rule-making, which in terms of content is the set of steps for the study, analysis, evaluation, public opinion, public demands, opinions, positions regarding the formation of public opinion, that is, the set of steps to raise legal awareness. The law-making phase operates in a different format and with the effectiveness and degree of influence in the context of different sources of law. Thus, in the countries of the Anglo-Saxon legal system, legal custom as a source of law is widely used in administrative and legal relations, from civil law relations to business circulation relations. It should be noted that in the Anglo-Saxon legal system, the most important and widely applicable tool of the law-making phase is also the operation of lobby organizations, whose operations are related not only to the operation of different national communities, but also to the operation of social communities. However, the activity of the latter is actively combined with the work of brain centers.
Keywords: Law making; lobbying; brain center; legitimacy; sociality; legal awareness; security system